The influence of social information on norms of cooperation [research data PhD project] - Eymess, Tillmann (Universität, 2021)
Replication package for the dissertation titled "The Influence of Social Information on Norms of Cooperation" by Tillmann Eymess, Heidelberg Univer...
Gesehen am 10.03.2022
Keywords: Forschungsdaten; Datenbank